1993
DOI: 10.1002/app.1993.070501009
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of radiolabeled cellulose acetate and cellulose propionate

Abstract: SYNOPSISBiodegradation of cellulose acetate and cellulose propionate was conclusively established with a naturally derived mixed microbial culture derived from activated sludge and 14C labeled cellulose esters. Radiolabeled cellulose esters were synthesized with either [ 1-14C] -acetate or [1-14C] -propionate and back hydrolyzed to the desired degree of substitution (DS) ranging from 1.77 to 2.64. Biodegradation was measured in an in uitro aerobic culture system that was designed to capture 14C02 produced by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(69 citation statements)
references
References 5 publications
3
66
0
Order By: Relevance
“…Gardner et al 156) showed, basing on film disintegration and on weight loss, that cellulose acetates, having DS less than approximately 2.20, compost at 53 8C and 60% moisture at rates comparable to that of PHBV. Komarek et al 155) provided via aerobic biodegradation of radiolabeled CA, that in CA with a DS of 1.85 more than 80% of the original 14 C-polymeric carbon was biodegraded to 14 CO 2 . The studies on biodegradation of CA although have been given much attention in recent times; scarce attention has been paid to the biodegradation of formulated resins consisting of cellulose acetate and diluents.…”
Section: Cellulose Acetatementioning
confidence: 99%
See 1 more Smart Citation
“…Gardner et al 156) showed, basing on film disintegration and on weight loss, that cellulose acetates, having DS less than approximately 2.20, compost at 53 8C and 60% moisture at rates comparable to that of PHBV. Komarek et al 155) provided via aerobic biodegradation of radiolabeled CA, that in CA with a DS of 1.85 more than 80% of the original 14 C-polymeric carbon was biodegraded to 14 CO 2 . The studies on biodegradation of CA although have been given much attention in recent times; scarce attention has been paid to the biodegradation of formulated resins consisting of cellulose acetate and diluents.…”
Section: Cellulose Acetatementioning
confidence: 99%
“…Cellulose esters, e. g., cellulose acetate (CA) are considered as potentially useful polymers in biodegradable applications [154][155][156][157][158][159][160] . CA is a modified polysaccharide synthesized by the reaction of acetic anhydride with cotton linters or wood pulp.…”
Section: Cellulose Acetatementioning
confidence: 99%
“…One of the more convincing degradation studies was the aerobic biodegradation of radiolabelled CA by Komarek, Gardner, and Buchanan where they monitored the evolution of CO 2 from in vitro samples with the acetyl carbons labeled with 14 C [5]. The study compared CA with degrees of substitutions of 1.85, 2.07 and 2.57, and found the biodegradation rates were reduced, but not inhibited, by the higher levels of acetyl (Fig.…”
Section: Biological Degradationmentioning
confidence: 99%
“…Later the importance of the deacetylation step was shown, when it was learned that acetyl esterase enzymes are common in microorganisms. Currently CA is generally recognized as a biodegradable polymer within the scientific community [4][5][6][7][8]. Recent work has allowed a considerable increase in the knowledge of the enzymology of non-substituted and acetylated polysaccharides, thus illuminating the biodegradation mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…The available test methods have also been further extended to include biodegradation tests of packaging materials and plastics and other consumer products in accelerated land-Ðll, short-term controlled composting (up to 45 days) and longer-term composting (up to 6 months).47 A very precise method has been developed by Komarek et al for the establishment of the biodegradability of cellulose esters. 48 In this work radiolabelled cellulose acetate and propionate were tested with a mixed microbial culture derived from activated sludge. The extent of biodegradation was highly dependent on the degree of substitution of the polymers, and this was proven conclusively by the detection of liberated 14CO 2 indicating the microbial species had utilized the polymer as a carbon source.…”
Section: Biodegradability Issues and Testingmentioning
confidence: 99%